Kinerja Kemandirian Keuangan Lembaga Keuangan Mikro (LKM) Berbasis Perempuan Studi Pada Wilayah Pesisir Kabupaten Tangerang - Mukhaer Pakkanna (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2015)
The one of the formal financial media that can reach (outreach) and welfare of poor rural communities is through MFIs (Microfinance Institutions). Of course, the MFI is the ‘healthy’ and financially independent. This study aims to reveal the performance of financial independence (MFIs semi-formal, especially the cooperative of the female members based) on the fishery area, North Tangerang, Banten. In addition, it also reveals the performance of MFIs in increasing the coverage to members. Hence, to address the issue of technical guidelines on the use of performance indicators (sustainability) of financial from regulation of the Minister of Cooperatives and Small and Medium Enterprises republic of Indonesia No. 20/Per/M.KUKM/XI/2008 and indicators organized by Ledgerwood (1999). The research found the fact that the MFI fishing communities (coastal) recorded the ‘healthy’category (KCP Pakuhaji = 93.40, KCP Mekar Baru = 85.90 and KCP Mauk = 79.90). In addition, the size of the financial health also seen a low level of bad debts (nonperforming loan) on a MFIs semi-formal members. The low nonperforming loan strongly associated with the institutional capacity to implement financing programs that already in the early design and is compatible with the wishes of the members.